Haemorrhagic enteritis of probable parvovirus origin in dogs - Omar, Abdul Rahman; Lee, Jeffery Y. S.; Ng, L. T. (Persatuan Doktor Veterinar Malaysia, 1980)
In recent months we have seen several cases of haemorrhagic enteritis in dogs -in and around Kuala Lumpur which presented clinical and pathological manifestions similar to those described for parvovirus enteritis in the United States (Eugester et al., 1978; Appel et al., 1979 and Cooper et al., 1979), Canada (Thomson and Gagnon, 1978), Australia (Kelly, 1978) and in the United Kingdom (Else, 1980).